Improvements and Future Challenges for the Research: Infrastructure in the Field of Civil Society - Mareike Alscher; Eckhard Priller (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
Despite the obvious existence of civil society organizations (CSOs) and forms of civic engagement, the data available for this sector remains inadequate. This expert report provides a comprehensive view of the current data situation, reveals existing gaps, and offers suggestions on how these gaps might be closed. The empirical material currently provided by existing data sources - the Federal Statistical Office, statistics from the CSOs themselves, as well as special data and surveys - only register this area separately and to a limited extent, and even then not in a consistent manner. With respect to both civil society organizations and forms of individual engagement there is an inadequate data situation. Questions that have arisen around whether CSOs will remain oriented toward civil society in a context of increased economic pressure on organizations cannot be answered. Similarly, it is nearly impossible to analyze whether civic engagement belies an increased tendency towards monetarization. Since civil society will undoubtedly continue to gain in political and social importance, the long-term task will be to set up a meaningful and a predominantly self-contained system of data collection and provision. This goal can be reached by following up on the existing surveys and databases described in this paper.
Keywords: 330; civil society; civil society organizations; civic engagement; Volunteers Survey; Johns Hopkins Comparative Nonprofit Sector Project; Handbook on Nonprofit Institutions in the System of National Accounts